Influence of selected socio-demographic factors and depression on evaluation of selected aspects of the quality of life of people with a history of thoracic-lumbar spine pathology treated surgically - Poznańska, Małgorzata (Nursing Problems / Problemy Pielęgniarstwa, 2013)
The main objective of this study was a comprehensive evaluation of some aspects of the quality of life in patients who have undergone surgical treatment of the vertebral column in the thoracic and/or lumbar segments, their condition caused by injuries, neoplasms, or inflammatory lesions. The sample of the prospective study comprised 143 surgical patients of the Clinic for Neurosurgery of the 5th Military Hospital with Polyclinic in Krakow, and the Clinic for Neurosurgery and Neurotraumatology of the University Hospital in Krakow, with disorders leading to damage to bony structures, the ligament-articular apparatus, and damage or the risk of damage of nerve elements in the thoracic and lumbar segments of the vertebral column On the basis of these studies the main predictive factors of the quality of life after surgical treatment turned out to be age, functional status measured with the Barthel ADL index, presence of depression as well as etiopathogenesis and the location of the disordered segment in the vertebral column. Gender and marital status of the patients were also important. The original study revealed the necessity of monitoring patients in regard of occurrence of major depressive disorder. Above all, this study established the need for a comprehensive evaluation of the patient’s condition, exceeding significantly the indications of their clinical condition.